A multi-responsive targeting drug delivery system for combination photothermal/chemotherapy of tumor. Issue 2 (22nd January 2023) - Yang, Yuanyuan; Wu, Siqi; Zhang, Qinlin; Chen, Zhaoxia; Wang, Caixia; Jiang, Sijing; Zhang, Yuhong
Abstract: To achieve efficient delivery and precise release of chemotherapy drugs at tumor sites, an active targeting multi-responsive drug delivery platform was developed. Here, doxorubicin hydrochloride (DOX) was loaded onto polydopamine (PDA), which were coated by the cystamine-modified hyaluronic acid (HA-Cys), designated as DOX@PDA-HA (PDH). The combination of PDA and HA-Cys endowed the nanoplatform photothermal conversion, tumor-targeting, and pH/redox/NIR sensitive drug release capacity. Moreover, HA could be degraded by the excess hyaluronidase (HAase) in the tumor microenvironment (TME), promoting DOX release, and further enhancing the effect of chemotherapy. Experimental results demonstrated PDH good biocompatibility, high loading rate, targeted drug delivery, and efficient tumor cell killing ability. This ingenious strategy based on PDH showed huge potential in photothermal/chemotherapy combination treatment of cancer.